PERCEIVED IMPACT OF CLASSROOM MANAGEMENT ON EFFECTIVE TEACHING: A STUDY OF FIVE SCHOOLS IN EDUCATION DISTRICT 11, LAGOS STATE, NIGERIA - Austin, Omomia O.; T. A., Omomia (European Scientific Journal, ESJ, 2014)
Effective classroom management consists of teacher behaviour that produces high level of the involvement of students in the activities of the classroom, minimum level of students’ behaviour that affects the teacher or other students as they interfere with their works and will often interfere with the efficient use of instructional time. Effective teachers who are effective classroom managers will involve such activities in all aspects of their work as planned rules and procedures which are carefully and systematically taught to the students. This paper therefore, examined the perceived impact of classroom management on effective teaching. The descriptive survey research design method was used. While the self-developed survey questionnaire (Perceived Impact of Classroom Management- PICM) was used to collect data. A total of fifty teachers were randomly selected from the five schools in Education District 11, Lagos State. The mean was calculated for each of the item on the questionnaire. The decision rule was that any mean of 2.5 and above was accepted. And the mean of below 2.5 was rejected. All the items on the questionnaire had mean above 2.5. This meant that they were all accepted. Thus the research questions were answered. Based on the findings, recommendations were made.